2016
DOI: 10.1038/srep30699
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidylcholine acts in the constitutive immune defence against American foulbrood in adult honeybees

Abstract: Honeybee (Apis mellifera) imagines are resistant to the Gram-positive bacterium Paenibacillus larvae (P. larvae), causative agent of American foulbrood (AFB), whereas honeybee larvae show susceptibility against this pathogen only during the first 48 h of their life. It is known that midgut homogenate of adult honeybees as well as a homogenate of aged larvae exhibit strong anti-P. larvae activity. A bioactivity-guided LC-HRMS analysis of midgut homogenate resulted in the identification of 1-oleoyl-sn-glycero-3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…We found out that, in general, the putatively annotated lysophospholipids were detected in higher abundance in C. lacinia pupae and butterflies. Taken together, our findings suggested that lysophospholipids, along with their structural function, may play important roles by protecting the insects against microorganisms, as corroborated by previous reports [53], during pupation and by acting as an energy source for diapause and metamorphosis. Moreover, 1-(9-octadecenoyl)-glycero-3-phosphoserine ( 23 ) and 1-stearoyl-2-hydroxy-glycero-3-phosphoethanolamine ( 26 ) were predominately found in C. lacinia butterflies, which indicated that these metabolites may be important substrates for flight in the adult life stage, as previously reported [51,52].…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…We found out that, in general, the putatively annotated lysophospholipids were detected in higher abundance in C. lacinia pupae and butterflies. Taken together, our findings suggested that lysophospholipids, along with their structural function, may play important roles by protecting the insects against microorganisms, as corroborated by previous reports [53], during pupation and by acting as an energy source for diapause and metamorphosis. Moreover, 1-(9-octadecenoyl)-glycero-3-phosphoserine ( 23 ) and 1-stearoyl-2-hydroxy-glycero-3-phosphoethanolamine ( 26 ) were predominately found in C. lacinia butterflies, which indicated that these metabolites may be important substrates for flight in the adult life stage, as previously reported [51,52].…”
Section: Resultssupporting
confidence: 90%
“…Besides, several insect pheromones and growth hormones exhibit lipophilic character [51,52]. Recently, lysophosphatidylcholine has been associated with antimicrobial activity in adult honeybees [53]. We found out that, in general, the putatively annotated lysophospholipids were detected in higher abundance in C. lacinia pupae and butterflies.…”
Section: Resultsmentioning
confidence: 85%
“…The most interesting case concerning virulence was strain 119 which can cause variable mortality depending on the host background (Figure ). In a previous study, M. plutonius strain 119 showed high virulence leading to mortality rates of 70% in 2 weeks (Riessberger‐Gallé, Hernández‐López, Rechberger, Crailsheim, & Schuehly, ). This corresponds to the higher virulence in colony B of the current study (Figure ).…”
Section: Discussionmentioning
confidence: 92%
“…48–72 hr old 1.92 × 10 5 CFU/larva 21 days 100% 1.94 × 10 5 CFU/larva 87.5% [ 44 ] No infection control N/A N/A N/A N/A N/A 0 CFU/larva 21 days ≤14.6% DAT561 (atypical) 12 12 Japan approx. 48–72 hr old 2.2–4.6 × 10 4 CFU/larva 21 days 77.1–80.6% [ 55 ] No infection control N/A N/A N/A N/A N/A 0 CFU/larva 14 days approx. 15% e 119 (typical) 20 13 Switzerland 5–10 hr old ~6.0 × 10 4 CFU/larva 14 days approx.…”
Section: Virulence Of Atypical M Plutoniusmentioning
confidence: 99%